B Cell Aberrance in Lupus: the Ringleader and the Solution - Nie, YuXue; Zhao, Lidan; Zhang, Xuan (Clinical reviews in allergy & immunology, 2022)
Systemic lupus erythematosus (SLE) is a prototypical autoimmune disease with high heterogeneity but the common characterization of numerous autoantibodies and systemic inflammation which lead to the damage of multiple organs. Aberrance of B cells plays a pivotal role in the immunopathogenesis of SLE via both antibody-dependent and antibody-independent manners. Escape of autoreactive B cells from the central and peripheral tolerance checkpoints, over-activation of B cells and their excessive cytokines release which drive T cells and dendritic cells stimulation, and dysregulated surface molecules, as well as intracellular signal pathways involved in B cell biology, are all contributing to B cell aberrance and participating in the pathogenesis of SLE. Based on that rationale, targeting aberrance of B cells and relevant molecules and pathways is expected to be a promising strategy for lupus control. Multiple approaches targeting B cells through different mechanisms have been attempted, including B-cell depletion via monoclonal antibodies against B-cell-specific molecules, blockade of B-cell survival and activation factors, suppressing T-B crosstalk by interrupting costimulatory molecules and inhibiting intracellular activation signaling cascade by targeting pathway molecules in B cells. Though most attempts ended in failure, the efficacy of B-cell targeting has been encouraged by the FDA approval of belimumab that blocks B cell-activating factor (BAFF) and the recommended use of anti-CD20 as a remedial therapy in refractory lupus. Still, quantities of clinical trials targeting B cells or relevant molecules are ongoing and some of them have displayed promising preliminary results. Additionally, advances in multi-omics studies help deepen our understandings of B cell biology in lupus and may promote the discovery of novel potential therapeutic targets. The combination of real-world data with basic research achievements may pave the road to conquering lupus.